The Discovery, Distribution, and Evolution of Viruses Associated with Drosophila melanogaster. - Claire L Webster; Fergal M Waldron; Shaun Robertson; Daisy Crowson; Giada Ferrari; Juan F Quintana; Jean-Michel Brouqui; Elizabeth H Bayne; Ben Longdon; Amy H Buck; Brian P Lazzaro; Jewelna Akorli; et al. (PLoS Biology)
Drosophila melanogaster is a valuable invertebrate model for viral infection and antiviral immunity, and is a focus for studies of insect-virus coevolution. Here we use a metagenomic approach to identify more than 20 previously undetected RNA viruses and a DNA virus associated with wild D. melanogaster. These viruses not only include distant relatives of known insect pathogens but also novel groups of insect-infecting viruses. By sequencing virus-derived small RNAs, we show that the viruses represent active infections of Drosophila. We find that the RNA viruses differ in the number and properties of their small RNAs, and we detect both siRNAs and a novel miRNA from the DNA virus. Analysis of small RNAs also allows us to identify putative viral sequences that lack detectable sequence similarity to known viruses. By surveying >2,000 individually collected wild adult Drosophila we show that more than 30% of D. melanogaster carry a detectable virus, and more than 6% carry multiple viruses. However, despite a high prevalence of the Wolbachia endosymbiont--which is known to be protective against virus infections in Drosophila--we were unable to detect any relationship between the presence of Wolbachia and the presence of any virus. Using publicly available RNA-seq datasets, we show that the community of viruses in Drosophila laboratories is very different from that seen in the wild, but that some of the newly discovered viruses are nevertheless widespread in laboratory lines and are ubiquitous in cell culture. By sequencing viruses from individual wild-collected flies we show that some viruses are shared between D. melanogaster and D. simulans. Our results provide an essential evolutionary and ecological context for host-virus interaction in Drosophila, and the newly reported viral sequences will help develop D. melanogaster further as a model for molecular and evolutionary virus research.